Activity of imipenem/relebactam against Pseudomonas aeruginosa producing ESBLs and carbapenemases. (5th November 2020) - Mushtaq, Shazad; Meunier, Danièle; Vickers, Anna; Woodford, Neil; Livermore, David M
Abstract: Background: ESBL- and carbapenemase-producing Pseudomonas aeruginosa are prevalent in, for example, the Middle East, Eastern Europe and Latin America, though rarer elsewhere. Because P. aeruginosa readily mutate to become carbapenem resistant via loss of OprD, isolates producing ESBLs are often as broadly resistant as those producing carbapenemases. We hypothesized that: (i) relebactam might overcome class A carbapenemases directly in P. aeruginosa ; and (ii) relebactam's inhibition of AmpC, which gives a generalized potentiation of imipenem against the species, might restore imipenem susceptibility in OprD-deficient ESBL producers. Methods: MICs were determined using CLSI agar dilution for P. aeruginosa isolates producing ESBLs, principally VEB types, and for those producing GES-5, KPC and other carbapenemases. Results: Relebactam potentiated imipenem by around 4–8-fold for most P. aeruginosa isolates producing VEB and other ESBLs; however, MICs were typically only reduced to 4–16 mg/L, thus mostly remaining above EUCAST's susceptible range and only partly overlapping CLSI's intermediate range. Strong (approx. 64-fold) potentiation was seen for isolates producing KPC carbapenemases, but only 2-fold synergy for those with GES-5. Predictably, potentiation was not seen for isolates with class B or D carbapenemase activity. Conclusions: Relebactam did potentiate imipenem against ESBL-producing P. aeruginosa, which are mostly imipenem resistant via OprD loss, but this potentiation was generally insufficient to reduce imipenem MICs to the clinical range. Imipenem resistance owing to KPC carbapenemases was reversed by relebactam in P. aeruginosa, just as for Enterobacterales.